A Candidate Giant Planet Companion to the Massive, Young White Dwarf GALEX J071816.4+373139 Informs the Occurrence of Giant Planets Orbiting B Stars - Sihao Cheng; Kevin C. Schlaufman; Ilaria Caiazzo (The Astronomical Journal)
It has been suggested that giant planet occurrence peaks for stars with M _* ≈ 3 M _⊙ at a value a factor of 4 higher than observed for solar-mass stars. This population of giant planets predicted to frequently orbit main-sequence B stars at a ≈ 10 au is difficult to characterize during the few hundred million years while fusion persists in their host stars. By the time those stars become massive, young white dwarfs, any giant planets present would still be luminous as a consequence of their recent formation. From an initial sample of 2195 Gaia-identified massive, young white dwarfs, we use homogeneous Spitzer Infrared Array Camera (IRAC) photometry to search for evidence of unresolved giant planets. For 30 systems, these IRAC data provide sensitivity to objects with M ≲ 10 M _Jup , and we identify one candidate with M ≈ 4 M _Jup orbiting the white dwarf GALEX J071816.4+373139. Correcting for the possibility that some of the white dwarfs in our sample result from mergers, we find a giant planet occurrence ${η }_{\,\rm{GP}\,}=0.1{1}_{-0.07}^{+0.13}$ for stars with initial masses M _* ≳ 3 M _⊙ . Our occurrence inference is consistent with both the Doppler-inferred occurrence of giant planets orbiting M _* ≈ 2 M _⊙ giant stars and the theoretically predicted factor of 4 enhancement in the occurrence of giant planets orbiting M _* ≈ 3 M _⊙ stars relative to solar-mass stars. Future James Webb Space Telescope NIRCam observations of our sample would provide sensitivity to Saturn-mass planets and thereby a definitive estimate of the occurrence of giant planets orbiting stars with M _* ≳ 3 M _⊙ .